2021
DOI: 10.1111/os.12908
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐Aided Minimally Invasive Lumbopelvic Fixation in Treatment of Traumatic Spinopelvic Dissociation

Abstract: Objective: To investigate the surgical strategy, safety, and efficacy of close reduction and robot-aided minimally invasive lumbopelvic fixation in treatment of traumatic spinopelvic dissociation. Methods: Data of 32 patients (21 males and 11 females) with traumatic spinopelvic dissociation treated by lumbopelvic fixation with robot-aided minimally invasive technique or conventional open procedure in our institution from March 2010 to April 2019 were retrospectively analyzed, and divided into robot group and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
5
19
0
Order By: Relevance
“…According to recorded frequency of intraoperative uoroscopy, the data in this study were signi cantly decreased in the robot group (P < 0.001), which was similar to the existing reports using the same technique [16,17,24]. All guide pins in the robot group were basically successfully implanted at one time, while that in the conventional group needs to be adjusted twice or more.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…According to recorded frequency of intraoperative uoroscopy, the data in this study were signi cantly decreased in the robot group (P < 0.001), which was similar to the existing reports using the same technique [16,17,24]. All guide pins in the robot group were basically successfully implanted at one time, while that in the conventional group needs to be adjusted twice or more.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, since bony landmarks at the surgical site used in the process of guide pin implantation often need to be visualized clearly with uoroscopy, patients and surgeons are subject to large amounts of harmful radiation. Consequently, the desire for decreasing complication rates, avoiding excessive radiation and improving accuracy lead to the development of computer navigation and robotassisted surgery [16,17]. Although some studies on robot-assisted pelvic fracture xation have already been reported, minimally invasive triangular osteosynthesis with robotic assistance for the treatment of USFs is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the retrograde anterior column screws aren’t suitable for the fixation of transverse acetabular fractures. Some recent studies reported that percutaneous fixation with surgical navigation is increasingly minimally invasive and safe [ 17 , 18 , 22 ]. Robot-aided orthopedic surgery has recently emerged as a more viable tool to enable higher precision surgery, as well as saving surgical time [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the uncertain entry point and the narrow bony corridor, it usually takes much time to insert the guiding wire accurately, with the consequence of excessive radiation exposure to patients and surgeons. Percutaneous fixation under the guidance of orthopedic robots has been reported with the advantages of accuracy and convenience [ 17 , 18 ]. Most important of all, robot-aided technology can also assist surgeons to plan, simulate and correct the trajectory of screws intraoperatively [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation